PENGEMBANGAN MEDIA FLASH CARD LACA BERBASIS WEB UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PESERTA DIDIK DISLEKSIA - Mutin Kartika Dewi; Sujarwanto; Murtadlo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop web-based Flash Card LACA learning media to improve the reading skills of dyslexic students at SD Negeri Balerejo 02. This media uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study showed that this media is effective in improving the reading skills of dyslexic students with an interactive and easily accessible design. The material test obtained a score of 85%, with several parts that need to be revised to suit the needs of dyslexic students. The media test showed a score of 91%, indicating that this media design is valid without revision. The practitioner test involved teachers and material experts who confirmed that this media was practical and effective, with a very good validity score. The student response questionnaire showed that 83.33% of students felt that this media helped them understand the material and increase their self-confidence, with a significant increase in the pretest and posttest results. The teacher response questionnaire showed that 97% of teachers considered this media suitable for use in learning, practical, and effective in supporting reading learning for dyslexic students. Overall, this study shows that the web-based LACA Flash Card media is valid, practical, and effective in improving the reading skills of dyslexic students, and is expected to be a reference for the development of similar learning media in other schools.